PELAKSANAAN DIAGNOSIS KESULITAN BELAJAR DAN PENGAJARAN REMEDIAL OLEH GURU BK DAN GURU MATA PELAJARAN (Studi Deskriptif Analitis pada Peserta Didik Kelas VIII di SMP Negeri 28 Padang) - Putri, Mita Anggela; Ibrahim, Indra; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
Problem in this research how the implantation of the diagnosis of learning difficulties and remedial teaching by guidance and counseling teachers and subject teachers in SMP Negeri 28 Padang. The purpose of this research was to describe: 1) guidance and counseling teachers activities in implementing the identification of students who have learning difficulties, 2) guidance and counseling teachers activities in localizing the location of students learning difficulties, 3) guidance and counseling teacher activities in localizing the causes factors of students learning difficulties, 4) guidance and counseling teachers activities in planning assistance and establish possible ways to overcome students learning difficulties, 5) assistance given by guidance and counseling teachers in the implementation of remedial teaching to students, 6) assistance given by subject teachers in the implementation of remedial teaching to students. Sample in this research with technique purposive sampling. Based on these objectives obtained a sample of 71 students. Data collection tool used was a questionnaire, while the data analysis technique using percentage analysis. Results of this research revealed that: 1) guidance and counseling teachers activities in implementing the identification of students who have learning difficulties in good enough category, 2) guidance and counseling teachers activities in localizing the location of students learning difficulties in good enough category, 3) guidance and counseling teacher activities in localizing the causes factors of students learning difficulties in good enough category, 4) guidance and counseling teachers activities in planning assistance and establish possible ways to overcome students learning difficulties in good enough category, 5) assistance given by guidance and counseling teachers in the implementation of remedial teaching to students in good enough category, 6) assistance given by subject teachers in the implementation of remedial teaching to students in good enough category. Based on the results of this research recommended to guidance and counseling teachers in to order improve the implementation diagnosis of learning difficulties to be effective and for subject teachers can do remedial teaching effective and efficient.